2021
DOI: 10.3389/fimmu.2021.651109
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stromal Cell Derived Membrane Particles Are Internalized by Macrophages and Endothelial Cells Through Receptor-Mediated Endocytosis and Phagocytosis

Abstract: Mesenchymal stromal cells (MSC) are a promising therapy for inflammatory diseases. However, MSC are large and become trapped in the lungs after intravenous infusion, where they have a short survival time. To steer MSC immunoregulatory therapy beyond the lungs, we generated nm-sized particles from MSC membranes (membrane particles, MP), which have immunomodulatory properties, and investigated their internalization and mode of interaction in macrophages subtypes and human umbilical vein endothelial cells (HUVEC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
(56 reference statements)
0
9
0
Order By: Relevance
“…Generally, according to different sizes of entrapped substances and uptake mechanisms, endocytosis can be divided into phagocytosis, macropinocytosis, and receptor-mediated endocytosis. 23 Since phagocytosis refers to the process of ingesting particulate matter larger than 1 μm in diameter, and the size of nano-sperms does not qualify, we explored the two other ways. First, to address whether nanosperms would enter cells through various receptor-mediated endocytosis processes, methyl-beta-cyclodextrin (MβCD, which inhibits clathrin-mediated endocytosis), chlorpromazine (CPM, which inhibits caveolae-mediated endocytosis), nystatin (NYS, which inhibits kinin-dependent endocytosis) and dynasore (DYN, which inhibits lipid raft-mediated endocytosis) were utilized, 24,25 and the fluorescence intensity changed to varying degrees.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, according to different sizes of entrapped substances and uptake mechanisms, endocytosis can be divided into phagocytosis, macropinocytosis, and receptor-mediated endocytosis. 23 Since phagocytosis refers to the process of ingesting particulate matter larger than 1 μm in diameter, and the size of nano-sperms does not qualify, we explored the two other ways. First, to address whether nanosperms would enter cells through various receptor-mediated endocytosis processes, methyl-beta-cyclodextrin (MβCD, which inhibits clathrin-mediated endocytosis), chlorpromazine (CPM, which inhibits caveolae-mediated endocytosis), nystatin (NYS, which inhibits kinin-dependent endocytosis) and dynasore (DYN, which inhibits lipid raft-mediated endocytosis) were utilized, 24,25 and the fluorescence intensity changed to varying degrees.…”
Section: Resultsmentioning
confidence: 99%
“…The uptake of miRNAs in the presence of serum was further validated in different cell types including HEK293T, A549, U87MG, Min6 and SGC-7901, using fluorescent miRNAs (Extended Data, figure 1c). As disrupting cellular microfilament networks can block endocytosis and micropinocytosis (Al Soraj et al , 2012; da Costa Goncalves et al , 2021), we further analyze the uptake of 5’-Cy5-miR-29a in the presence of serum after treating Hela cells with cytochalasin B, rottlerin, dynarose, nocodazole or other cytoskeleton disrupting reagents. After 1 h incubation, we found that rottlerin and nocodazole, two macropinocytosis inhibitor (Hufnagel et al , 2009), strongly prevented cellular uptake of 5’-Cy5-miR-29a, whereas other reagents displayed no inhibition on 5’-Cy5-miR-29a uptake (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, recent data suggested that mesenchymal stromal cell‐derived membrane particles might be internalised by endothelial cells through receptor‐mediated endocytosis and phagocytosis. 26 Accordingly, membrane particle uptake by endothelial cells involved the actin cytoskeleton and phosphoinositide 3‐kinase, which are implicated in macropinocytosis and phagocytosis. In the present study, MV.Act induced an increase in the F/G‐actin ratio in HMVECs consistent with actin polymerisation and cytoskeleton rearrangement.…”
Section: Discussionmentioning
confidence: 99%